Cultural Institutions of the Novel - Warner, William Beatty; Lynch, Deidre (Book collections on Project MUSE., 1996)
The story of the development of the novel--its origin, rise, and increasing popularity as a narrative form in an ever-expanding range of geographic and cultural sites--is familiar and, according to the contributors to this volume, severely limited. In a far-reaching blend of comparative literature and transnational cultural studies, this collection shifts the study of the novel away from a consideration of what makes a particular narrative a novel to a consideration of how novels function and what cultural work they perform--from what novels are, to what they do.The essays in Cultural Institutions of the Novel find new ways to analyze how a genre notorious for its aesthetic unruliness has become institutionalized--defined, legitimated, and equipped with a canon. With a particular focus on the status of novels as commodities, their mediation of national cultures, and their role in transnational exchange, these pieces range from the seventeenth century to the present and examine the forms and histories of the novel in England, Nigeria, Japan, France, New Zealand, Canada, and the United States. Works by Jane Austen, Natsume Sôseki, Gabriel García Márquez, Buchi Emecheta, and Toni Morrison are among those explored as Cultural Institutions of the Novel investigates how theories of "the" novel and disputes about which narratives count as novels shape social struggles and are implicated in contests over cultural identity and authority.Contributors. Susan Z. Andrade, Lauren Berlant, Homer Brown, Michelle Burnham, James A. Fujii, Nancy Glazener, Dane Johnson, Lisa Lowe, Deidre Lynch, Jann Matlock, Dorothea von Mücke, Bridget Orr, Clifford Siskin, Katie Trumpener, William B. Warner.